Millimeter Cloud Radar measurements - NSF Arctic Data Center (Arctic Data Center, 2010)
This data set contains raw measurements from a Millimeter Cloud Radar (MMCR) that is deployed at Summit Station, Greenland. This radar operates at 35 GHz (Ka-band) and points vertically with a 0.3 degree beamwidth. Four alternating operational modes are employed to optimally observe different types of tropospheric clouds. Data files contain the following measured parameters: Radar reflectivity, signal-to-noise ratio, mean Doppler velocity, and Doppler spectrum width. Detailed information on these parameters and other aspects of the dataset are included in the netCDF header information for each file. The MMCR is owned by the National Oceanic and Atmospheric Administrations's Earth System Research Laboratory. Field operations are supported by the National Science Foundation's Arctic Observing Network (AON) Program.